Validation of a Hebrew version of the Early Childhood Oral Health Impact Scale - Gaon, Ofir; Natapov, Lena; Ram, Diana; Zusman, Shlomo Paul; Fux-Noy, Avia (Frontiers in Oral Health, 2025)
BackgroundDental problems such as early childhood caries in toddlers and children can significantly impact their and their family's oral health-related quality of life.AimThis study aimed to validate a Hebrew version of the Early Childhood Oral Health Impact Scale (ECOHIS), providing a reliable tool for assessing oral health-related quality of life in toddlers and preschool children.DesignThe ECOHIS questionnaire was translated from English to Hebrew using the “forward–backward translation” method. Two pediatric dentistry specialists evaluated the face and content validity of the Hebrew ECOHIS. Parents of children under 6 years old visiting the pediatric dentistry department at a medical center completed the Hebrew version of the ECOHIS questionnaire and provided their child's personal information. The decayed, missing, and filled teeth (dmft) index was extracted from the dental record.ResultsThe study group consisted of 96 children, whose parents participated, including 50 boys and 46 girls, with a mean age of 3.6 years. A positive correlation was found between higher ECOHIS scores and higher dmft indices. No differences were observed between ECOHIS scores and variables such as gender, age, and social subgroups of the participants. The overall scale reliability was high (Cronbach's alpha = .83). Confirmatory factor analysis supported the questionnaire's two-factor structure and indicated a moderate fit to the data.ConclusionThe Hebrew version of the ECOHIS was found to be valid and reliable for measuring oral health-related quality of life in toddlers and preschool children in Israel.